Treatment of Fracture Sequel in the Mandibular Angle Region. (4th July 2019) - Sangalette, Beatriz Sobrinho; Levatti, Tiago Trevizan; Vieira, Larissa Vargas; Filho, João Lopes Toledo; Pastori, Cláudio Maldonado; Toledo, Gustavo Lopes
Abstract : Because of the anterior disposition on the face and the fragility of the anatomy, the mandible is commonly affected in facial fractures, and the angle region represents 32% of the mandibular fractures; therefore, the objective of the paper was to present a proposal for late correction of the mandibular fracture already consolidated and with occlusal alteration. Patient J.C.P.R., 32, during anamnesis reported loss of sensibility in the mentalis region as well as unilateral posterior open bite for having been a victim of an automobile accident about 1 year and 3 months ago. Physical examination showed elevation in the right mandibular angle region due to the poor positioning of fractured stumps. It has been found that the patient suffered a simple fracture at the mandibular angle, but that had not been treated previously, and it was necessary to treat the fracture sequel. Refraction was performed with a new reduction and fixation through titanium plates and screws, showing that, even being late, the procedure to reduce the fracture sequela was effective, even with the correct functional occlusal adjustment.